Low-temperature curing type composite rock-soil anti-seepage reinforcing material and preparation method thereof
Patent Information
- Application Number
- CN202611147061.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]本发明旨在提供一种低温固化型复合岩土防渗增强材料及制备方法,以解决或改善上述技术问题中现有岩土防渗加固材料在低温环境下固化活性不足、浆液稳定性差、固化体易收缩开裂且防渗增强耐久性不足的问题
通过将低温固化型复合岩土防渗增强材料设置为分别预混合的低温活性组分液和固化增强组分液,使低温活性主剂与复合固化引发剂在施工前分开储存,避免材料在储存和运输过程中提前聚合或失效,提高了材料的储存稳定和现场施工可控。
Smart Images

Figure CN122978796A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of soil and rock reinforcement materials technology, and more specifically, to a low-temperature curing composite soil and rock seepage prevention and reinforcement material and its preparation method. Background Technology
[0002] Seepage prevention and reinforcement in geotechnical engineering is commonly used in cold regions with weak strata, deep foundation pits, dams, and mine tailings dams to reduce soil permeability and improve the stability of the rock and soil mass. Existing seepage prevention and reinforcement materials mainly include inorganic, organic, and composite materials. Inorganic materials are mostly cement and water glass, which have the advantage of low cost, but their hydration or gelation reaction activity decreases at low temperatures, the curing cycle is long, and the cured body is prone to shrinkage and cracking. Organic materials such as acrylates and polyurethanes have good impermeability, but they are usually expensive, have insufficient durability, and some components pose environmental risks. Composite materials often employ simple compounding methods, resulting in poor component compatibility and low-temperature gel controllability, and are prone to problems such as delamination, agglomeration, or incomplete curing. To address these issues, a low-temperature curing composite soil-rock impermeable reinforcement material and its preparation method are proposed. Summary of the Invention
[0003] The present invention aims to provide a low-temperature curing composite geotechnical anti-seepage reinforcement material and its preparation method, so as to solve or improve the problems of insufficient curing activity, poor slurry stability, easy shrinkage and cracking of the cured body and insufficient anti-seepage reinforcement durability of existing geotechnical anti-seepage reinforcement materials in the above-mentioned technical problems.
[0004] In view of this, the first aspect of the present invention is to provide a low-temperature curing composite geotechnical impermeable reinforcement material.
[0005] A second aspect of the present invention is to provide a low-temperature curing composite soil and rock seepage prevention and reinforcement material.
[0006] A first aspect of the present invention provides a low-temperature curing composite soil-rock impermeable reinforcement material, comprising premixed low-temperature active component liquid and curing reinforcement component liquid; based on a total weight of 100 parts of the low-temperature active component liquid, the low-temperature active component liquid comprises the following components in parts by weight: 22 to 36 parts of low-temperature active agent, 3.5 to 7.2 parts of composite retarding stabilizer, 2.1 to 4.8 parts of flexible toughening agent, and 52 to 68 parts of deionized water; based on a total weight of 100 parts of the curing reinforcement component liquid, the curing reinforcement component liquid... The product comprises the following components in parts by weight: 8 to 16 parts of composite curing initiator, 12 to 24 parts of active reinforcing filler, 1.2 to 3.5 parts of pH adjuster, and 58 to 78 parts of deionized water; wherein, the low-temperature active agent includes a copolymer of hydroxyethyl methacrylate and itaconic acid, the composite curing initiator includes potassium persulfate, sodium bisulfite, and tert-butyl peroxide, the active reinforcing filler includes ultrafine metakaolin and nano silica, and the volume mixing ratio of the low-temperature active component liquid to the curing reinforcing component liquid is 1:0.8 to 1:1.3.
[0007] The first aspect of the present invention provides a preparation method comprising the following steps: adding deionized water to a mixing tank at 0°C to 5°C and stirring; adding a low-temperature active agent and stirring, followed by ultrasonic-assisted dissolution and stirring of a composite retarding stabilizer; adding a flexible toughening agent for homogeneous dispersion, and filtering to obtain a low-temperature active component liquid; adding deionized water to a mixing tank at 5°C to 10°C and stirring; adding a composite curing initiator and stirring until dissolved; adding an active reinforcing filler and ultrasonically dispersing; adding a pH adjuster to adjust the pH value and filtering to obtain a curing reinforcing component liquid; storing the low-temperature active component liquid and the curing reinforcing component liquid separately, and mixing them at a volume ratio of 1:0.8 to 1:1.3 before construction.
[0008] The beneficial effects of this invention compared to the prior art are as follows: By setting the low-temperature curing composite soil and rock seepage prevention reinforcement material as a premixed low-temperature active component liquid and a curing reinforcement component liquid, the low-temperature active agent and the composite curing initiator are stored separately before construction, which avoids the material from prematurely polymerizing or failing during storage and transportation, thereby improving the storage stability of the material and the controllability of on-site construction.
[0009] By using a copolymer of hydroxyethyl methacrylate and itaconic acid as a low-temperature active agent, the material can maintain high polymerization activity at low temperatures. Furthermore, the carboxyl groups introduced by itaconic acid enhance the bonding ability between organic components and inorganic fillers, thereby improving the problems of slow and insufficient low-temperature curing of existing materials.
[0010] By using potassium persulfate, sodium bisulfite, and tert-butyl peroxide as a composite curing initiator, a relatively stable free radical initiation system can be formed under low temperature conditions, thereby improving low-temperature curing efficiency and shortening the molding time under low-temperature conditions.
[0011] By using ultrafine metakaolin and nano silica as active reinforcing fillers, an inorganic reinforcing skeleton can be formed in the solidified body and fill the micropores, reducing the internal pore connectivity of the solidified body and improving the compressive strength, impermeability and water erosion resistance of the solidified body.
[0012] By setting composite retarder stabilizers, flexible toughening agents, and pH adjusters, and limiting the volume mixing ratio of low-temperature active component liquid and curing reinforcement component liquid, the fluidity, gel time, penetration and diffusion capacity, and volume stability after curing of the slurry can be taken into account. This reduces the problems of low-temperature curing shrinkage cracking, delamination and agglomeration, and insufficient seepage prevention durability, making the material more suitable for seepage prevention and reinforcement construction in low-temperature complex geological environments such as soft strata in cold regions, deep foundation pits, dams, and mine tailings ponds.
[0013] Additional aspects and advantages of embodiments of the invention will become apparent in the following description or may be learned by practice of embodiments of the invention. Attached Figure Description
[0014] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which: Figure 1 This is a flowchart of the preparation method of the temperature-curing composite soil and rock seepage prevention reinforcement material of the present invention; Figure 2 This is a flowchart of the preparation steps of the low-temperature active component solution of the present invention; Figure 3 This is a flowchart of the preparation steps of the curing and reinforcing component liquid of the present invention. Detailed Implementation
[0015] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and therefore the scope of protection of the invention is not limited to the specific embodiments disclosed below.
[0016] The following describes a low-temperature curing composite geotechnical seepage-proofing reinforcement material and its preparation method according to some embodiments of the present invention.
[0017] An embodiment of the first aspect of the present invention provides a low-temperature curing composite soil-rock seepage-proofing reinforcement material. In some embodiments of the present invention, the low-temperature curing composite soil-rock seepage-proofing reinforcement material comprises premixed low-temperature active component liquid and curing reinforcement component liquid.
[0018] Based on a total weight of 100 parts, the low-temperature active component solution includes the following components in parts by weight: 22 to 36 parts of low-temperature active agent, 3.5 to 7.2 parts of composite retarder stabilizer, 2.1 to 4.8 parts of flexibility toughening agent, and 52 to 68 parts of deionized water.
[0019] Based on a total weight of 100 parts, the curing and reinforcing component liquid includes the following components in parts by weight: 8 to 16 parts of composite curing initiator, 12 to 24 parts of active reinforcing filler, 1.2 to 3.5 parts of pH adjuster, and 58 to 78 parts of deionized water.
[0020] The low-temperature active agent includes a copolymer of hydroxyethyl methacrylate and itaconic acid; the composite curing initiator includes potassium persulfate, sodium bisulfite and tert-butyl peroxide; the active reinforcing filler includes ultrafine metakaolin and nano silica; and the volume mixing ratio of the low-temperature active component liquid to the curing reinforcing component liquid is 1:0.8 to 1:1.3.
[0021] The present invention provides a low-temperature curing composite geotechnical seepage prevention and reinforcement material, which prepares and stores the low-temperature active component liquid and the curing and reinforcement component liquid separately. This can avoid the low-temperature active agent and the composite curing initiator from undergoing premature polymerization or cross-linking reaction during storage, thereby improving the storage stability of the material and the controllability of on-site construction. Before construction, the components are mixed according to a preset volume ratio, which can form a mixed slurry with suitable gelation time and penetration diffusion ability according to the grouting construction rhythm.
[0022] Based on a total weight of 100 parts, the low-temperature active component solution comprises 22 to 36 parts of a low-temperature active agent, 3.5 to 7.2 parts of a composite retarder and stabilizer, 2.1 to 4.8 parts of a flexibility and toughening agent, and 52 to 68 parts of deionized water. The low-temperature active agent, serving as the main component for film and gel formation, is a binary copolymer of hydroxyethyl methacrylate and itaconic acid. This copolymer contains active groups capable of participating in low-temperature free radical polymerization and carboxyl functional groups capable of interacting with the hydroxyl groups on the surface of inorganic fillers. This allows the low-temperature active agent to form an organic polymer network at low temperatures and to form a composite bond with the inorganic fillers in the subsequent curing and reinforcing component solution.
[0023] Composite retarder stabilizers are used to regulate the reaction rate after mixing the low-temperature active component liquid and the curing and reinforcing component liquid, ensuring that the slurry maintains a certain flow time before being injected into the pores or weak interlayers of the soil and rock, preventing excessively rapid gelation after mixing, which could cause pipeline blockage or insufficient diffusion radius. Furthermore, composite retarder stabilizers can improve the dispersion stability of the slurry under low-temperature conditions, reducing the risk of local agglomeration or premature polymerization of the low-temperature active agent. Flexible toughening agents are embedded in the cured polymer network structure, forming flexible connection nodes within the cured body to alleviate shrinkage stress generated during low-temperature curing, reduce the risk of cracking, and improve the toughness and durability of the cured body under formation deformation, water erosion, or freeze-thaw disturbances. Deionized water, as the dispersion medium, can reduce the interference of impurity ions such as calcium, magnesium, and iron ions in the system on the polymerization reaction and slurry stability, and ensure that the low-temperature active component liquid has a viscosity suitable for grouting diffusion.
[0024] Based on a total weight of 100 parts, the curing and reinforcing component solution includes 8 to 16 parts of a composite curing initiator, 12 to 24 parts of an active reinforcing filler, 1.2 to 3.5 parts of a pH adjuster, and 58 to 78 parts of deionized water. The composite curing initiator includes potassium persulfate, sodium bisulfite, and tert-butyl peroxide. Potassium persulfate provides a source of free radicals at low temperatures, sodium bisulfite promotes the decomposition of potassium persulfate at low temperatures and increases the efficiency of free radical generation, and tert-butyl peroxide acts as an auxiliary initiator to supplement the free radical supply, enabling the low-temperature active agent to remain stably cured at temperatures ranging from 0°C to 15°C.
[0025] The active reinforcing filler includes ultrafine metakaolin and nano-silica. Ultrafine metakaolin acts as an inorganic reinforcing framework in the construction of the solidified body structure, improving its compressive strength and resistance to water erosion. Nano-silica, with its small particle size and large specific surface area, fills the micropores formed between organic polymer networks and metakaolin particles, thereby refining the pore size distribution of the solidified body, reducing seepage channel connectivity, and improving seepage prevention performance. A pH adjuster is used to adjust the solidification and reinforcing component liquid and the mixed slurry to a suitable weakly acidic to neutral range, preventing the initiator from decomposing too quickly or reacting insufficiently due to unsuitable pH, and reducing the adverse effects of strong acid and alkaline environments on construction equipment and the surrounding soil and rock environment.
[0026] The volume mixing ratio of the low-temperature active component liquid to the curing and reinforcing component liquid is controlled at 1:0.8 to 1.3. This ratio range can achieve a balance between the content of the low-temperature active agent, the initiator content, and the active reinforcing filler content: when the amount of curing and reinforcing component liquid is too low, it is easy to lead to insufficient initiation and insufficient reinforcing filler content, resulting in a decrease in the strength and impermeability of the cured body; when the amount of curing and reinforcing component liquid is too high, it may lead to excessively rapid reaction, shortened grout injection time, or excessive filler content, affecting grout fluidity. By limiting the volume mixing ratio of the two within the above range, the mixed grout can have low-temperature curability, workability, good penetration and diffusion, and impermeability and reinforcing performance after curing.
[0027] The number average molecular weight of the low-temperature active agent is 8,000 to 12,000, and the molecular weight distribution index is 1.2 to 1.5; the solid content of the copolymer of hydroxyethyl acrylate and itaconic acid in the low-temperature active agent is 28 wt% to 42 wt%.
[0028] In the embodiments provided by the present invention, the number average molecular weight of the low-temperature active agent can be 8000, 9500, 10500 or 12000, and the molecular weight distribution index can be 1.2, 1.3, 1.4 or 1.5.
[0029] After controlling the molecular weight as described above, the low-temperature active agent can maintain a good dispersion state and low-temperature reactivity in the low-temperature active component solution. Among them, when the number average molecular weight is 9500 to 10500 and the molecular weight distribution index is 1.3 to 1.4, the matching between the slurry viscosity, penetration and diffusion capacity and the structural strength after curing is good.
[0030] The low-temperature active agent is prepared as a deionized aqueous solution with a solid content of 28wt%, 32wt%, 36wt%, 40wt%, or 42wt%.
[0031] Using the aforementioned low-temperature active agent solution with the specified solid content ensures sufficient effective gelling components in the low-temperature active component solution, preventing a significant increase in slurry viscosity under low-temperature conditions due to excessively high solid content. Especially when the solid content is between 32 wt% and 40 wt%, the low-temperature active component solution, after mixing, balances injectability and curing network capabilities, which is beneficial for forming a continuous and stable polymer curing network within the pores of soil and rock.
[0032] The composite retarding stabilizer includes sodium citrate, sodium gluconate, and sodium pyrophosphate; the weight ratio of sodium citrate, sodium gluconate, and sodium pyrophosphate is 1.2:0.8:1.5 to 2.5:1.5:3.2.
[0033] In the embodiments provided by the present invention, the composite retarding stabilizer is formed by compounding sodium citrate, sodium gluconate and sodium pyrophosphate, and the weight ratio of the three can be 1.2:0.8:1.5, 1.5:1.0:2.0, 1.8:1.2:2.5, 2.2:1.4:3.0 or 2.5:1.5:3.2.
[0034] When using the above-mentioned compound system, sodium citrate can chelate metal ions in the system and reduce the interference of metal ions on the low-temperature polymerization rate; sodium gluconate can delay the free radical polymerization reaction under low-temperature conditions, so that the mixed slurry can maintain a suitable injection time; sodium pyrophosphate can improve the dispersion stability of the slurry, reduce the risk of component agglomeration, precipitation or stratification under low-temperature conditions, and enable the gelation time of the mixed slurry at 5°C to be stably controlled at about 22 min to 55 min.
[0035] The flexibility toughening agent is polyethylene glycol diglycidyl ether; the molecular weight of polyethylene glycol diglycidyl ether is 600 to 1000 and the epoxy value is 0.25 eq / 100g to 0.35 eq / 100g.
[0036] In the embodiments provided by the present invention, the flexible toughening agent is polyethylene glycol diglycidyl ether, and the molecular weight of polyethylene glycol diglycidyl ether can be 600, 750, 850 or 1000, and the epoxy value can be 0.25eq / 100g, 0.28eq / 100g, 0.32eq / 100g or 0.35eq / 100g.
[0037] When polyethylene glycol diglycidyl ether is used as a flexible toughening agent, its polyether segments can form a flexible connection structure in the cured network, and the epoxy active groups can participate in or embed into the composite cross-linking system formed by low-temperature curing, thereby reducing the shrinkage stress of the cured body during the low-temperature molding process. When the molecular weight is 750 to 850 and the epoxy value is 0.28 eq / 100g to 0.32 eq / 100g, the flexible toughening agent has good dispersibility in the low-temperature active component liquid, and can improve the toughness of the cured body without significantly increasing the viscosity of the slurry, keeping the volume shrinkage rate of the cured body at about 6.5% to 7.5%, and reducing the risk of brittleness and microcracks after low-temperature curing.
[0038] The weight ratio of potassium persulfate, sodium bisulfite, and tert-butyl peroxide is 5:2:1 to 9:4:3.
[0039] In the embodiments provided by the present invention, the composite curing initiator is formed by compounding potassium persulfate, sodium bisulfite and tert-butyl peroxide, and the weight ratio of the three can be 5:2:1, 6:2.5:1.5, 7:3:2, 8:3.5:2.5 or 9:4:3.
[0040] When using the above-mentioned composite curing initiation system, potassium persulfate can serve as the main source of free radicals, initiating the polymerization reaction of the low-temperature active agent under low-temperature conditions. Sodium bisulfite can form a redox initiation system with potassium persulfate, reducing the difficulty of free radical generation at low temperatures and improving the initiation efficiency in environments below 5°C. Tert-butyl peroxide can serve as an auxiliary initiation component, supplementing the supply of free radicals and promoting the full progress of the curing reaction. When the weight ratio of the three components is 6:2.5:1.5, 7:3:2, or 8:3.5:2.5, the mixed slurry can maintain a relatively stable gel time and curing efficiency at 5°C, and the curing rate can reach approximately 92.8% to 95.7% in 24 hours. This is beneficial for improving the reliability of the material in low-temperature seepage prevention and reinforcement in cold regions, deep foundation pits, and water-rich strata in mines.
[0041] The weight ratio of ultrafine metakaolin to nano silica is 8:4 to 15:9; the particle size of ultrafine metakaolin is 2μm to 5μm and the specific surface area is 150m² / g to 250m² / g; the particle size of nano silica is 20nm to 50nm, the specific surface area is 200m² / g to 300m² / g, and the surface hydroxyl content is greater than 5mmol / g.
[0042] In the embodiments provided by the present invention, the active reinforcing filler is formed by compounding ultrafine metakaolin and nano-silica, and the weight ratio of the two can be 8:4, 10:5, 12:7, 14:8 or 15:9; the particle size of ultrafine metakaolin can be 2μm, 3μm, 4μm or 5μm, and the specific surface area can be 150m² / g, 180m² / g, 220m² / g or 250m² / g; the particle size of nano-silica can be 20nm, 30nm, 40nm or 50nm, the specific surface area can be 200m² / g, 240m² / g, 270m² / g or 300m² / g, and the surface hydroxyl content can be 5.2mmol / g, 5.8mmol / g, 6.5mmol / g or 7.0mmol / g.
[0043] When the above filler parameters are used, ultrafine metakaolin can form a micron-scale inorganic reinforcing skeleton in the solidified body, improving the compressive strength and water erosion resistance of the solidified body. Nano-silica can fill the micropores between polymer networks and metakaolin particles with its small particle size and high specific surface area, and form an interface with the carboxyl groups in the low-temperature active agent through surface hydroxyl groups, thereby reducing pore connectivity and improving seepage prevention performance. When the weight ratio of ultrafine metakaolin to nano-silica is 10:5, 12:7 or 14:8, the dispersion stability of the mixed slurry is good, the 7-day compressive strength of the solidified body can reach about 0.55 MPa to 0.64 MPa, and the permeability coefficient can be reduced to about 4.2 × 10^-8 cm / s to 4.9 × 10^-8 cm / s.
[0044] The pH adjuster is potassium dihydrogen phosphate, and the pH value of the curing and reinforcing component solution is 4.0 to 5.0; the pH value of the slurry after mixing the low-temperature active component solution and the curing and reinforcing component solution is 5.5 to 7.0.
[0045] In the embodiments provided by the present invention, the pH adjuster is potassium dihydrogen phosphate, and the pH value of the curing and reinforcing component liquid can be adjusted to 4.0, 4.3, 4.5, 4.8 or 5.0; the pH value of the slurry after mixing the low-temperature active component liquid and the curing and reinforcing component liquid can be 5.5, 5.8, 6.2, 6.6 or 7.0.
[0046] Using potassium dihydrogen phosphate as a pH adjuster ensures that the curing and reinforcing component solution remains within a weakly acidic range, reducing the risk of rapid decomposition of the composite curing initiator before storage or mixing. After the two components are mixed, the slurry pH is in the weakly acidic to neutral range, which is conducive to the stable low-temperature free radical polymerization reaction and reduces the adverse effects of strong acid or strong alkali conditions on grouting equipment and the geotechnical environment. When the pH of the mixed slurry is 5.8, 6.2, or 6.6, the slurry reaction rate is relatively stable, and a relatively stable gel time can be maintained at 5℃. Furthermore, no significant alkali leaching or acid corrosion is observed in the cured body, which is beneficial for improving the material's environmental friendliness and long-term seepage prevention stability in cold regions, soft soil foundations, and water-rich strata in mines.
[0047] The initial viscosity of the slurry after mixing the low-temperature active component liquid and the curing and reinforcing component liquid is 30 mPa·s to 50 mPa·s, and the gelation time of the slurry at 5℃ is 15 min to 60 min.
[0048] In the embodiments provided by the present invention, the initial viscosity of the slurry after mixing the low-temperature active component liquid and the curing and reinforcing component liquid can be 30 mPa·s, 35 mPa·s, 40 mPa·s, 45 mPa·s or 50 mPa·s, and the gelation time of the slurry at 5°C can be 15 min, 22 min, 28 min, 33 min, 42 min, 48 min, 55 min or 60 min.
[0049] When the above viscosity and gel time are controlled, the mixed grout can maintain good fluidity and injectability at low temperatures. When the initial viscosity is between 35 mPa·s and 45 mPa·s, the grout is suitable for entering the pores, weak interlayers, and micro-cracks of fine sand. When the gel time is between 22 min and 48 min, the grout can gradually solidify after penetration and diffusion, avoiding blockage of the grouting pipeline or insufficient diffusion radius caused by excessively rapid gelation, and also avoiding grout loss, leakage, or difficulty in forming the seepage prevention boundary caused by excessively slow gelation. This allows the material to balance workability, formation penetration and filling effect, and enhanced seepage prevention after solidification at a low temperature of 5℃.
[0050] After mixing the low-temperature active component liquid and the curing and reinforcing component liquid, the mixture is cured at 0°C to 15°C to form a composite cured body. The composite cured body includes a three-dimensional network organic polymer skeleton formed by polymerization of the low-temperature active agent, an inorganic cross-linked structure formed by the carboxyl groups in the low-temperature active agent and the active reinforcing filler, and nano-silica filling the pores of the three-dimensional network organic polymer skeleton.
[0051] In the embodiments provided by the present invention, the low-temperature active component liquid and the curing and reinforcing component liquid can be mixed and cured at 0°C, 5°C, 10°C or 15°C to form a composite cured body.
[0052] During the curing process, the low-temperature active agent undergoes free radical polymerization under the action of the composite curing initiator, forming a continuous three-dimensional network organic polymer skeleton. The carboxyl groups in the low-temperature active agent combine with the hydroxyl groups on the surface of active reinforcing fillers such as ultrafine metakaolin and nano silica to form an inorganic cross-linked structure in which the organic and inorganic phases are synergistically linked. Nano silica further fills the micropores of the three-dimensional network organic polymer skeleton, reducing the internal pore connectivity of the cured body. The body can simultaneously obtain the impermeability of the organic polymer network, the reinforcement of the inorganic filler structure, and the density brought by the pore filling of nanoparticles.
[0053] In specific tests, the curing rate of the composite cured body can reach approximately 92.8%, 94.2%, or 95.7% after 24 hours at 5℃; the 7-day compressive strength can reach approximately 0.55 MPa, 0.58 MPa, or 0.64 MPa; the permeability coefficient can be reduced to approximately 4.9 × 10⁻⁸ cm / s, 4.7 × 10⁻⁸ cm / s, or 4.2 × 10⁻⁸ cm / s; and the volume shrinkage rate can be controlled at approximately 7.5%, 7.3%, or 6.9%.
[0054] The second aspect of the present invention provides a method for preparing the low-temperature curing composite soil-rock impermeable reinforcement material described in any of the above embodiments. For example... Figure 1 As shown, in some embodiments of the present invention, the preparation method includes: S101, under conditions of 0℃ to 5℃, deionized water is added to the mixing tank and stirred, low-temperature active agent is added and stirred, ultrasonic-assisted dissolution and composite retarding stabilizer are added and stirred; flexible toughening agent is added for homogeneous dispersion, and after filtration, low-temperature active component liquid is obtained.
[0055] S102, deionized water is added to the mixing tank at 5℃ to 10℃ and stirred, composite curing initiator is added and stirred until dissolved; active reinforcing filler is added and ultrasonically dispersed, pH adjuster is added to adjust the pH value and filtered to obtain curing and reinforcing component liquid.
[0056] S103, the low-temperature active component liquid and the curing and reinforcing component liquid are stored separately and mixed at a volume ratio of 1:0.8 to 1:1.3 before construction.
[0057] The present invention provides a preparation method in which low-temperature active component liquid and curing enhancement component liquid are prepared under corresponding low-temperature conditions, which can reduce the risk of premature reaction of low-temperature active agent, premature decomposition of composite curing initiator and agglomeration and sedimentation of active enhancement filler. During the preparation of the low-temperature active component liquid, stirring and ultrasonic-assisted dissolution are used to uniformly disperse the low-temperature active agent, composite retarder stabilizer and flexible toughening agent, which is beneficial to improving the uniformity of the subsequent low-temperature polymerization reaction and the toughness of the cured body. During the preparation of the curing and reinforcing component liquid, the composite curing initiator is kept stable and active by stirring and dissolving, ultrasonic dispersion and pH adjustment, and the ultrafine metakaolin and nano silica are uniformly dispersed, thereby improving the reinforcing and filling effect and impermeability after curing. By storing the low-temperature active component liquid and the curing and reinforcing component liquid separately and mixing them in proportion before construction, the material storage stability and on-site gelation time controllability can be taken into account, so that the mixed grout has good fluidity, penetration and diffusion ability and low-temperature curing performance during low-temperature grouting.
[0058] Specifically, such as Figure 2 As shown, the steps for preparing the low-temperature active component solution include: S201, clean the mixing tank with deionized water and purge it with nitrogen; after controlling the temperature inside the mixing tank at 0℃ to 5℃, add deionized water and stir at a stirring rate of 300r / min to 400r / min. S202, add the low-temperature active agent in 3 portions, stirring after each addition. After all the agents are added, stir for 15 to 20 minutes at 0 to 5 degrees Celsius, and then use ultrasound to assist dissolution at a power of 200W and a frequency of 20kHz. S203, add sodium citrate, sodium gluconate and sodium pyrophosphate in sequence, and stir for 5 to 8 minutes after each component is added to form a uniform dispersion system of composite retarder stabilizer; S204, heat the system to 10℃ to 15℃, add the flexible toughening agent and stir for 10 min to 15 min, then filter to obtain the low-temperature active component solution.
[0059] Specifically, such as Figure 3 As shown, the steps for preparing the curing and reinforcing component liquid include: S301, clean the mixing tank with deionized water and purge it with nitrogen; after controlling the temperature inside the mixing tank at 5℃ to 10℃, add deionized water and stir at a stirring rate of 400r / min to 500r / min. S302, potassium persulfate, sodium bisulfite and tert-butyl peroxide are added in sequence, and stirred at 5℃ to 10℃ for 12 min to 18 min to form a uniform solution system of composite curing initiator; S303 is added in batches with ultrafine metakaolin and ultrasonically dispersed, and then nano-silica is added and ultrasonically dispersed again to form a uniform dispersion system of active reinforced filler. S304, heat the system to 15℃ to 20℃, add potassium dihydrogen phosphate as a pH adjuster, and adjust the pH of the curing and reinforcing component solution to 4.0 to 5.0. After filtration, the curing and reinforcing component solution is obtained.
[0060] Furthermore, before construction, the low-temperature active component liquid and the curing and reinforcing component liquid are placed in the construction environment, so that the temperature difference between the low-temperature active component liquid and the curing and reinforcing component liquid and the construction environment temperature is no more than 2°C, and then mixed and grouted using a dual-liquid grouting machine and a static mixer.
[0061] Furthermore, the grouting pressure of the dual-liquid grouting machine is 0.2MPa to 0.5MPa, the residence time of the grout after mixing the low-temperature active component liquid and the curing and reinforcing component liquid in the static mixer and grouting pipe is no more than 5 minutes, and the grouting rate is 5L / min to 10L / min.
[0062] To further illustrate the present invention, the following detailed description, in conjunction with specific embodiments, illustrates the low-temperature curing composite geotechnical seepage prevention and reinforcement material and its preparation method provided by the present invention. The hydroxyethyl methacrylate, itaconic acid, sodium citrate, sodium gluconate, sodium pyrophosphate, polyethylene glycol diglycidyl ether, potassium persulfate, sodium bisulfite, tert-butyl peroxide, ultrafine metakaolin, nano-silica, potassium dihydrogen phosphate, and deionized water used in the following embodiments can all be commercially available products or prepared according to conventional methods in the art. In each embodiment, the low-temperature active component liquid and the curing and reinforcement component liquid are prepared separately according to the preparation method of the present invention, and mixed at a set volume ratio before construction or testing to evaluate the gel time, curing rate, compressive strength, permeability coefficient, and volume shrinkage rate of the resulting mixed slurry under low-temperature conditions.
[0063] Example 1 Preparation of low-temperature active component solution: Weigh 28.5 parts of low-temperature active agent, 5.2 parts of composite retarder stabilizer, 3.1 parts of flexible toughening agent and 63.2 parts of deionized water, and prepare low-temperature active component solution according to the above-mentioned preparation method.
[0064] Preparation of curing and reinforcing component liquid: Weigh 11.3 parts of composite curing initiator, 18.6 parts of active reinforcing filler, 2.1 parts of pH adjuster and 68.0 parts of deionized water, and prepare curing and reinforcing component liquid according to the aforementioned preparation method.
[0065] The low-temperature active component liquid and the curing and reinforcing component liquid were mixed at a volume ratio of 1:1.05 to obtain a mixed slurry. Tests showed that the mixed slurry had a gel time of 28 min, a curing rate of 94.2% at 5℃ for 24 h, a 7-day compressive strength of 0.58 MPa, a permeability coefficient of 4.7 × 10⁻⁸ cm / s, and a volume shrinkage rate of 7.3%.
[0066] Example 2 Preparation of low-temperature active component solution: Weigh 25.8 parts of low-temperature active agent, 4.6 parts of composite retarder stabilizer, 2.7 parts of flexible toughening agent and 66.9 parts of deionized water, and prepare low-temperature active component solution according to the above-mentioned preparation method.
[0067] Preparation of curing and reinforcing component liquid: Weigh 9.7 parts of composite curing initiator, 15.4 parts of active reinforcing filler, 1.8 parts of pH adjuster and 73.1 parts of deionized water, and prepare the curing and reinforcing component liquid according to the aforementioned preparation method.
[0068] The low-temperature active component liquid and the curing and reinforcing component liquid were mixed at a volume ratio of 1:0.92 to obtain a mixed slurry. Tests showed that the mixed slurry had a gel time of 22 min, a curing rate of 92.8% after 24 h at 5℃, a 7-day compressive strength of 0.51 MPa, a permeability coefficient of 5.1 × 10⁻⁸ cm / s, and a volume shrinkage rate of 7.8%.
[0069] Example 3 Preparation of low-temperature active component solution: Weigh 32.1 parts of low-temperature active agent, 6.5 parts of composite retarder stabilizer, 4.2 parts of flexible toughening agent and 57.2 parts of deionized water, and prepare low-temperature active component solution according to the above-mentioned preparation method.
[0070] Preparation of curing and reinforcing component liquid: Weigh 14.5 parts of composite curing initiator, 22.3 parts of active reinforcing filler, 2.8 parts of pH adjuster and 60.4 parts of deionized water, and prepare the curing and reinforcing component liquid according to the aforementioned preparation method.
[0071] The low-temperature active component liquid and the curing and reinforcing component liquid were mixed at a volume ratio of 1:1.2 to obtain a mixed slurry. Tests showed that the mixed slurry had a gel time of 42 min, a curing rate of 95.7% at 5℃ for 24 h, a 7-day compressive strength of 0.64 MPa, a permeability coefficient of 4.2 × 10⁻⁸ cm / s, and a volume shrinkage rate of 6.9%.
[0072] Example 4 Preparation of low-temperature active component solution: Weigh 34.7 parts of low-temperature active agent, 7.0 parts of composite retarder stabilizer, 4.5 parts of flexible toughening agent and 53.8 parts of deionized water, and prepare low-temperature active component solution according to the above-mentioned preparation method.
[0073] Preparation of curing and reinforcing component liquid: Weigh 15.2 parts of composite curing initiator, 23.5 parts of active reinforcing filler, 3.2 parts of pH adjuster and 58.1 parts of deionized water, and prepare the curing and reinforcing component liquid according to the aforementioned preparation method.
[0074] The low-temperature active component liquid and the curing and reinforcing component liquid were mixed at a volume ratio of 1:1.28 to obtain a mixed slurry. Tests showed that the mixed slurry had a gel time of 55 min, a curing rate of 96.3% at 5℃ for 24 h, a 7-day compressive strength of 0.67 MPa, a permeability coefficient of 3.9 × 10⁻⁸ cm / s, and a volume shrinkage rate of 6.5%.
[0075] Example 5 Preparation of low-temperature active component solution: Weigh 27.3 parts of low-temperature active agent, 4.9 parts of composite retarder stabilizer, 3.5 parts of flexible toughening agent and 64.3 parts of deionized water, and prepare low-temperature active component solution according to the above-mentioned preparation method.
[0076] Preparation of curing and reinforcing component liquid: Weigh 12.8 parts of composite curing initiator, 17.2 parts of active reinforcing filler, 2.4 parts of pH adjuster and 67.6 parts of deionized water, and prepare curing and reinforcing component liquid according to the aforementioned preparation method.
[0077] The low-temperature active component liquid and the curing and reinforcing component liquid were mixed at a volume ratio of 1:1.12 to obtain a mixed slurry. Tests showed that the mixed slurry had a gel time of 33 min, a curing rate of 93.8% at 5℃ for 24 h, a 7-day compressive strength of 0.55 MPa, a permeability coefficient of 4.9 × 10⁻⁸ cm / s, and a volume shrinkage rate of 7.5%.
[0078] Example 6 Preparation of low-temperature active component solution: Weigh 30.6 parts of low-temperature active agent, 5.8 parts of composite retarder stabilizer, 3.9 parts of flexible toughening agent and 59.7 parts of deionized water, and prepare low-temperature active component solution according to the above-mentioned preparation method.
[0079] Preparation of curing and reinforcing component liquid: Weigh 10.4 parts of composite curing initiator, 20.8 parts of active reinforcing filler, 2.0 parts of pH adjuster and 66.8 parts of deionized water, and prepare the curing and reinforcing component liquid according to the aforementioned preparation method.
[0080] The low-temperature active component liquid and the curing and reinforcing component liquid were mixed at a volume ratio of 1:1.0 to obtain a mixed slurry. Tests showed that the mixed slurry had a gel time of 30 min, a curing rate of 94.5% at 5℃ for 24 h, a 7-day compressive strength of 0.60 MPa, a permeability coefficient of 4.5 × 10⁻⁸ cm / s, and a volume shrinkage rate of 7.1%.
[0081] Example 7 Preparation of low-temperature active component solution: Weigh 24.9 parts of low-temperature active agent, 4.2 parts of composite retarder stabilizer, 2.9 parts of flexible toughening agent and 68.0 parts of deionized water, and prepare low-temperature active component solution according to the above-mentioned preparation method.
[0082] Preparation of curing and reinforcing component liquid: Weigh 9.1 parts of composite curing initiator, 16.5 parts of active reinforcing filler, 1.7 parts of pH adjuster and 72.7 parts of deionized water, and prepare curing and reinforcing component liquid according to the aforementioned preparation method.
[0083] The low-temperature active component liquid and the curing and reinforcing component liquid were mixed at a volume ratio of 1:0.95 to obtain a mixed slurry. Tests showed that the mixed slurry had a gel time of 25 min, a curing rate of 92.1% after 24 h at 5℃, a 7-day compressive strength of 0.49 MPa, a permeability coefficient of 5.3 × 10⁻⁸ cm / s, and a volume shrinkage rate of 7.9%.
[0084] Example 8 Preparation of low-temperature active component solution: Weigh 33.2 parts of low-temperature active agent, 6.7 parts of composite retarder stabilizer, 4.4 parts of flexible toughening agent and 55.7 parts of deionized water, and prepare low-temperature active component solution according to the above-mentioned preparation method.
[0085] Preparation of curing and reinforcing component liquid: Weigh 13.6 parts of composite curing initiator, 21.4 parts of active reinforcing filler, 2.9 parts of pH adjuster and 62.1 parts of deionized water, and prepare curing and reinforcing component liquid according to the aforementioned preparation method.
[0086] The low-temperature active component liquid and the curing and reinforcing component liquid were mixed at a volume ratio of 1:1.18 to obtain a mixed slurry. Tests showed that the mixed slurry had a gel time of 48 min, a curing rate of 95.1% after 24 h at 5℃, a 7-day compressive strength of 0.62 MPa, a permeability coefficient of 4.1 × 10⁻⁸ cm / s, and a volume shrinkage rate of 6.7%.
[0087] Comparative Example 1 Preparation of low-temperature active component solution: Weigh 23.4 parts of low-temperature active agent, 3.8 parts of composite retarder stabilizer, 2.3 parts of flexible toughening agent and 70.5 parts of deionized water, and prepare low-temperature active component solution according to the above-mentioned preparation method.
[0088] Preparation of curing and reinforcing component liquid: Weigh 8.6 parts of composite curing initiator, 13.7 parts of active reinforcing filler, 1.5 parts of pH adjuster and 76.2 parts of deionized water, and prepare curing and reinforcing component liquid according to the aforementioned preparation method.
[0089] The low-temperature active component liquid and the curing and reinforcing component liquid were mixed at a volume ratio of 1:0.85 to obtain a mixed slurry. Tests showed that the mixed slurry had a gel time of 18 min, a curing rate of 91.5% after 24 h at 5℃, a 7-day compressive strength of 0.46 MPa, a permeability coefficient of 5.6 × 10⁻⁸ cm / s, and a volume shrinkage rate of 8.2%.
[0090] As can be seen from Examples 1 to 8, the low-temperature curing composite geotechnical seepage-proofing reinforcement material provided by the present invention can achieve stable gelation and effective curing at a low temperature of 5℃. The gelation time can be controlled between 22 min and 55 min, the 24-hour curing rate is not less than 92.1%, the 7-day compressive strength is not less than 0.49 MPa, the permeability coefficient is not higher than 5.3 × 10^-8 cm / s, and the volume shrinkage rate is not higher than 7.9%. Among them, Examples 3, 4, and 8 show higher curing rates, compressive strengths, and lower permeability coefficients, indicating that after increasing the dosage of the low-temperature active agent, composite retarder stabilizer, composite curing initiator, and active reinforcing filler, the material's low-temperature curing sufficiency, seepage-proof compactness, and structural reinforcement effect are further improved. Although Comparative Example 1 still has a certain low-temperature curing ability, its 7-day compressive strength is lower, and its permeability coefficient and volume shrinkage rate are relatively higher, indicating that when the amount of deionized water in the low-temperature active component solution is too high, the concentration of the effective gelling component decreases, and the compactness and seepage-proofing reinforcement effect of the cured body decrease accordingly.
[0091] The above embodiments are merely descriptions of preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A low-temperature curing composite soil-rock impermeable reinforcement material, characterized in that, This includes separately premixed low-temperature active component liquid and curing and reinforcing component liquid; Based on a total weight of 100 parts, the low-temperature active component solution comprises the following components in parts by weight: 22 to 36 parts of low-temperature active agent, 3.5 to 7.2 parts of composite retarder stabilizer, 2.1 to 4.8 parts of flexibility toughening agent, and 52 to 68 parts of deionized water. Based on a total weight of 100 parts, the curing and reinforcing component liquid comprises the following components in parts by weight: 8 to 16 parts of composite curing initiator, 12 to 24 parts of active reinforcing filler, 1.2 to 3.5 parts of pH adjuster, and 58 to 78 parts of deionized water. The low-temperature active agent includes a copolymer of hydroxyethyl methacrylate and itaconic acid; the composite curing initiator includes potassium persulfate, sodium bisulfite and tert-butyl peroxide; the active reinforcing filler includes ultrafine metakaolin and nano silica; and the volume mixing ratio of the low-temperature active component liquid to the curing reinforcing component liquid is 1:0.8 to 1:1.
3.
2. The low-temperature curing composite soil-rock seepage-proofing reinforcement material according to claim 1, characterized in that, The number-average molecular weight of the low-temperature active agent is 8,000 to 12,000, and the molecular weight distribution index is 1.2 to 1.
5. The solid content of the copolymer of hydroxyethyl acrylate and itaconic acid in the low-temperature active agent is 28wt% to 42wt%.
3. The low-temperature curing composite soil-rock seepage-proofing reinforcement material according to claim 1, characterized in that, The composite retarding stabilizer includes sodium citrate, sodium gluconate, and sodium pyrophosphate; The weight ratio of sodium citrate, sodium gluconate and sodium pyrophosphate is from 1.2:0.8:1.5 to 2.5:1.5:3.
2.
4. The low-temperature curing composite soil-rock seepage-proofing reinforcement material according to claim 1, characterized in that, The flexible toughening agent is polyethylene glycol diglycidyl ether; The polyethylene glycol diglycidyl ether has a molecular weight of 600 to 1000 and an epoxy value of 0.25 eq / 100g to 0.35 eq / 100g.
5. The low-temperature curing composite soil-rock seepage-proofing reinforcement material according to claim 1, characterized in that, The weight ratio of potassium persulfate, sodium bisulfite, and tert-butyl peroxide is from 5:2:1 to 9:4:
3.
6. The low-temperature curing composite soil-rock seepage-proofing reinforcement material according to claim 1, characterized in that, The weight ratio of the ultrafine metakaolin to the nano silica is 8:4 to 15:9; The ultrafine metakaolin has a particle size of 2μm to 5μm and a specific surface area of 150m² / g to 250m² / g; The nano-silica has a particle size of 20nm to 50nm, a specific surface area of 200m² / g to 300m² / g, and a surface hydroxyl content greater than 5mmol / g.
7. The low-temperature curing composite soil-rock seepage-proofing reinforcement material according to claim 1, characterized in that, The pH adjuster is potassium dihydrogen phosphate, and the pH value of the curing and reinforcing component solution is 4.0 to 5.0; The pH value of the slurry after mixing the low-temperature active component liquid and the curing and reinforcing component liquid is 5.5 to 7.
0.
8. The low-temperature curing composite soil-rock impermeable reinforcement material according to claim 1, characterized in that, The initial viscosity of the slurry after mixing the low-temperature active component liquid and the curing and reinforcing component liquid is 30 mPa·s to 50 mPa·s, and the gelation time of the slurry at 5°C is 15 min to 60 min.
9. The low-temperature curing composite soil-rock seepage-proofing reinforcement material according to any one of claims 1 to 8, characterized in that, The low-temperature active component liquid and the curing and reinforcing component liquid are mixed and then cured at 0°C to 15°C to form a composite cured body. The composite cured body includes a three-dimensional network organic polymer skeleton formed by polymerization of the low-temperature active agent, an inorganic cross-linked structure formed by the carboxyl groups in the low-temperature active agent and the active reinforcing filler, and nano-silica filling the pores of the three-dimensional network organic polymer skeleton.
10. A method for preparing the low-temperature curing composite geotechnical seepage-proofing reinforcement material according to any one of claims 1 to 9, characterized in that, Includes the following steps: Deionized water was added to the mixing tank at 0℃ to 5℃ and stirred. The low-temperature active agent was added and stirred, followed by ultrasonic-assisted dissolution and stirring of the composite retarding stabilizer. A flexible toughening agent was added for homogeneous dispersion, and the mixture was filtered to obtain the low-temperature active component solution. Deionized water was added to the mixing tank at 5℃ to 10℃ and stirred. The composite curing initiator was added and stirred until dissolved. The active reinforcing filler was added and ultrasonically dispersed. The pH value was adjusted by adding a pH adjuster and filtered to obtain the curing and reinforcing component liquid. The low-temperature active component liquid and the curing and reinforcing component liquid are stored separately and mixed at a volume ratio of 1:0.8 to 1:1.3 before construction.